In Vitro Germination and Flowering of Dendrobium capra J.J. Smith, An Endemic Orchid of Java - Muhammad Dylan Lawrie; Zulfa Layina; Della Rosiana Ningtias; Falah Nur Alifianto; Ari Indrianto; Aziz Purwantoro; Endang Semiarti (HAYATI Journal of Biosciences, 2021)
Dendrobium capra is an Indonesian endemic orchid species that live in Java. It grows on low altitude with warm climate. D. capra has beautiful small yellow greenish flower that grow in raceme inflorescence. This orchid faces a threat in its natural habitat due to having a long life cycle and a forestry main commodity as a main host thus categorized as Appendix II on CITES list. To address that problem, ex situ conservation approach using in vitro culture method is necessary. Germination enhancement effort using complex organic substances found that 200 ml/l tomato extract gave best germination result. Analysis on D. capra plantlet growth also showed that MS medium produced better plantlet size than NP, VW and KC medium. Supplementing medium with a combination of NAA and TDZ has also successfully induced early flowering within 11 month of culture period. This information is important to achieve successful in vitro culture of D. capra for various purposes.